Thermal stresses due to non-uniform internal heat generation in functionally graded hollow cylinder - Rani, P.; Singh, K.; Muwal, R. (Zielona Góra: Uniwersytet Zielonogórski)
Thermal stresses of a functionally graded hollow thick cylinder due to non-uniform internal heat generation are studied in this paper. Analytical solutions are obtained with radially varying properties by using the theory of elasticity.
Keywords: functionally graded material; non-uniform heat source; thermal stresses; hollow thick cylinder; temperature